2008
DOI: 10.1897/06-617.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arsenic speciation and low dissolved oxygen condition on the toxicity of arsenic to a lotic mayfly

Abstract: The influence of site-specific conditions on contaminant bioavailability and toxicity to benthic invertebrates is a key consideration in the environmental risk assessment process. This is particularly relevant for contaminants with complex speciation chemistries, such as arsenic. The present study addressed uncertainties regarding arsenic toxicity to a mayfly (Baetis tricaudatus) under low dissolved oxygen (DO) conditions characteristic of many contaminated sites. Arsenic toxicity (arsenite, As(III); arsenate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The mean measures at time zero and at 48 h for the control, 10, 20, 150, 500 and 1,000 lg l -1 groups were 1.4 ± 0.1, 13.5 ± 0.2, 27.7 ± 1.4, 154.1 ± 4.8, 514.0 ± 3.4, and 1,026.2 ± 1.7 lg l -1 (n = 2, mean ± standard error), respectively. A recent study (Irving et al 2008) found that the As (III) and As (V) speciation ratio remained stable between 48-h water renewals. In their study there was less than 1% of As (V) converted to As (III) within 48 h and no organic arsenic species were detected.…”
Section: Treatment Solutionmentioning
confidence: 96%
See 2 more Smart Citations
“…The mean measures at time zero and at 48 h for the control, 10, 20, 150, 500 and 1,000 lg l -1 groups were 1.4 ± 0.1, 13.5 ± 0.2, 27.7 ± 1.4, 154.1 ± 4.8, 514.0 ± 3.4, and 1,026.2 ± 1.7 lg l -1 (n = 2, mean ± standard error), respectively. A recent study (Irving et al 2008) found that the As (III) and As (V) speciation ratio remained stable between 48-h water renewals. In their study there was less than 1% of As (V) converted to As (III) within 48 h and no organic arsenic species were detected.…”
Section: Treatment Solutionmentioning
confidence: 96%
“…From two randomly selected tanks of each treatment, approximately 1 g of dried whole metamorphs (3-4 individuals) was randomly sampled for metal analysis. Tissue As concentrations were analyzed at the Soil and Plant Analysis Lab of the University of Wisconsin by ICP-MS after an openvessel HNO 3 plus H 2 O 2 hot-plate digestion (Irving et al 2008) following the procedures described in their on-line document Wisconsin Procedures for Soil Testing, Plant Analysis and Feed & Forage Analysis (detailed analysis procedures are available at http://uwlab.soils.wisc.edu/ madison/). Briefly, five ml of concentrated nitric acid was added to half a gram of dried tissue sample.…”
Section: Toxicity Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some arsenic is released into the environment from natural geogenic sources, e.g., volcanic activity (World Health Organization, 1981;Sanders et al, 1994), the major contributors to arsenic contamination of environment are anthropogenic activities, such as mining, smelting, and the production of fertilizers and pesticides (Agency for Toxic Substances and Disease Registry, 2007;Irving et al, 2008;Chen et al, 2009). Arsenic is toxic to most organisms and in mammals it causes diverse effects, including cancer and cardiovascular disease (Hughs, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…() reported mentum deformities in Chironomus dilutus that were exposed to arsenite spiked soils. The mayfly Baetis tricaudatus (Ephemeroptera: Baetidae) experienced reduced nymph growth and development when exposed to 1 000 μ g/L of arsenate and arsenite (Irving et al ., ). The mechanisms by which arsenic induces toxicity are varied (Kumagai & Sumi, ) and are not well understood in insects, although research suggests glutathione synthetase may play a role in detoxification (Muñiz‐Ortiz et al ., ; Andrahennadi & Pickering, ).…”
Section: Discussionmentioning
confidence: 97%